The Collaborative Development of Active Learning at Loyola University Chicago as Part of the SEMINAL Network. Issue 3 (28th May 2021) - Lange, Karin E.; Deiger, Megan; Bourque, Matthew; Tingley, Peter; Peters, Emily; Jordan, Laurie E.; Giaquinto, Anthony
ABSTRACT: In the context of national collaborative efforts to increase the prevalence of active learning strategies in undergraduate precalculus and calculus classrooms, we discuss the context, strategy, and processes used at one university to create change within a mathematics department. We highlight the use of a unified active learning approach and the importance of collaborative practices as leverage for departmental change. We conclude with lessons learned from the first year of implementation.